Clay mineralogy and texture of deep-sea hydrothermal mudstone associated with the Cerro Matoso peridotite in accreted oceanic crust from Colombia. (August 2022) - Castrillón, Andrés; Pi-Puig, Teresa; Guerrero, Javier; Nuñez-Useche, Fernando; Rodriguez, Augusto; Canet, Carles
Resumen: A partir de nuevos afloramientos en el Pit-1 de la mina de níquel a cielo abierto de Cerro Matoso, hemos muestreado los sedimentos que se encuentran sobre las peridotitas para estudiar las relaciones texturales y la composición de los filosilicatos que conforman lo que proponemos como una sucesión marina profunda. La estructura y mineralogía de montículos y estratos asociados permite dividir los sedimentos en dos litofacies, que están formadas principalmente por arcillolitas verdes y lodolitas negras. Los análisis químicos, mineralógicos y petrográficos, permitieron identificar berthierina y greenalita como los principales componentes de la fraccion arcilla de estas rocas. Ambos filosilicatos presentan picos agudos en los diagramas de difractometría de rayos-x (XRD), lo que indica que tienen un alto grado de "cristalinidad", que se da cuando éstos se forman bajo condiciones ideales de temperatura, pH alcalino, y ambientes reductores, los cuales, difieren de los ambientes supergénicos y oxidantes en los que ahora se encuentran. El contenido fosilífero, en el cual predominan bivalvos, gasterópodos y poliquetos, junto a las texturas fisuradas y brechadas de los sedimentos, acompañadas de una red de microfisuras y conductos abiertos, son indicativos de ambientes marinos con exhalación de fluidos, que se pueden relacionar con sistemas hidrotermales y procesos de serpentinización de rocas ultramáficas en el fondo marino. Este trabajo permite redefinir algunas unidades descritas anteriormente como parte del perfil laterítico de Cerro Matoso i.e ¨saprolito negro¨y ¨canga mona¨ y, además, reportar lo que sería el primer hallazgo de fauna asociada a ventilas hidrotermales en rocas del manto, adosadas posteriormente durante el Cretácico al continente. Estas fueron recientemente expuestas a condiciones tropicales húmedas en donde desarrollaron particulares perfiles de alteración laterítica. Abstract: New outcrops at the Cerro Matoso open-pit nickel mine permitted to sample sediments found on top of the peridotites to study the textural relationships and composition of phyllosilicates that make up what we propose is a deep marine succession. The appearance and color of mounds and tabular layers divided them into two lithofacies formed by green claystone and black mudstone. The chemical, mineralogical, and petrographic analysis allowed the identification of berthierine and greenalite as the main components of the clay fraction of these rocks. Both phyllosilicates show sharp peaks in the X-ray diffractometry (XRD) diagrams, which show a high degree of "crystallinity". These peaks are produced when the phyllosilicates are formed under ideal conditions of temperature, alkaline pH, and reducing environments, which differ from the supergene and oxidizing environments in which they are now found. The fossiliferous content, in which bivalves, gastropods, and polychaetes predominate, together with the fissured and brecciated textures in the sediments, accompanied by a network of microcracks and open ducts are indicative of marine environments with fluid exhalation that can be related to hydrothermal systems and serpentinization of ultramafic rocks. This work allows us to redefine some units previously described as part of the lateritic profile of Cerro Matoso, i.e., ¨black saprolite and ¨canga mona¨ and to report what would be the first discovery of fauna associated with hydrothermal vents hosted in mantle rocks that were posteriorly accreted during the Cretaceous to the continent. These were recently exposed to humid tropical environmental conditions, where they developed weathering lateritic profiles. Highlights: Reducing conditions and high temperatures instead of oxidizing environments are identified during the formation of clays at the top of the Cerro Matoso peridotites. Fossiliferous evidence helps to support ocean-deep environments in the Cerro Matoso sediments. Units previously considered as alteration products of ultramafic rocks are redefined as deep-marine sediments (black mudstone and green claystone). The findings coincide with the serpentinization processes that mantle rocks undergo in ocean ridges and that can host hydrothermal systems and associated fauna. Evidence of fauna associated with hydrothermal vents is reported, and it would be the first reported in Colombia.